Análise imunohistoquímica da ADAMTS-1 e proteoglicanos no ameloblastoma e no tumor odontogênico cístico calcificante - SOUZA NETO, Osvaldo Rodrigues de (Universidade Federal do Pará, 2014)
Ameloblastoma and calcifying cystic odontogenic tumor (CCOT) are odontogenic tumors with origin odontogenic epithelium, but it is not yet known stimulus or trigger that lead to neoplastic transformation of tumors. The biological behavior of the lesions is distinct because the ameloblastoma is more aggressive and significant rate of tumor recurrence. CCOT is a less aggressive tumor and recurrence rarely there and therefore was used as a control in the study. Therefore, the complete elucidation of the mechanisms by which these odontogenic tumors show such biological behavior remains a challenge for researchers. The ADAMTS (A Disintegrin and Metalloproteinase with thrombospondin) are metalloendopeptidases who are dependent on zinc in its catalytic domain. These enzymes have catalytic activity against a broad range of substrates including proteoglycans (aggrecan, brevican and versican), which are proteins present in the extracellular matrix (ECM). The ADAMTS exhibit structural features that confer great potential to display multiple functions. Exhibit crucial role in various processes such as proliferation, adhesion, invasion and cell signaling. Changes to these enzymes are present in various tumors, suggesting that these proteins may be involved in the carcinogenic process in different ways. Specifically, ADAMTS-1 has been correlated with tumorigenesis of some cancers such as in breast, lung and pancreatic cancer. Like ADAMTS, aggrecan, versican and brevican are expressed in various tumors and altered regulation of proteoglycans may contribute to the development of carcinogenesis. In this work ADAMTS-1, aggrecan, brevican and versican in ameloblastoma and CCOT were studied, 20 cases of ameloblastoma and 6 cases of TOCC, used as controls were included. We evaluated the expression of ADAMTS-1, aggrecan, brevican and versican by immunohistochemical study and the marking areas were measured and analyzed. To correlation analysis between the studied proteins used the Spearman test. All samples of ameloblastoma expressed ADAMTS-1, aggrecan, brevican and versican. All samples TOCC also expressed the same proteins, but in significantly less than the amount ameloblastoma. The difference in expression of ADAMTS-1 and brevican in the epithelium of ameloblastoma and of TOCC was statistically significant (p<0.0105). As the expression of aggrecan and versican, between ameloblastoma and TOCC, in the epithelium was also statistically significant (p<0.0067) and (p<0.0148), respectively. There was no correlation between the proteins studied.